Kemandirian Keuangan Daerah Pemerintah Kota Tasikmalaya Tahun Anggaran 2019-2022 - Talitha Nisriinaa Almira; Dedi Sukarno (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to describe the regional financial independence of the Tasikmalaya City Government for the 2019-2022 fiscal year. Considering that the PAD of Tasikmalaya City is still at a low level in contributing to regional income in Tasikmalaya City in the 2019-2022 fiscal year compared to the element of transfer funds and the regional financial capacity of the Tasikmalaya City Government in managing all sources of local revenue is considered not optimal. This research uses a qualitative approach with a case study research design. This study uses the calculation of the ratio of regional financial independence, the ratio of the degree of fiscal decentralization, the ratio of regional financial dependence, the ratio of PAD effectiveness, and the ratio of PAD efficiency which refers to the theory of Mahmudi (2016). Data collection techniques used in this research are documentation and interviews. The results of the research show that the Tasikmalaya City Government during the 2019-2022 fiscal year has an average regional financial independence is 23.46% with an instructive relationship pattern, the average degree of fiscal decentralization is 18.20% with a category of financial capability is less, the average financial dependence is still classified as very high with a ratio is 77.96%, the average effectiveness of PAD is 98.06% with a moderately effective category, and the average PAD efficiency is 1.82% with a very efficient category.